Synergistic anticancer effect of flavonoids from Sophora alopecuroides with Sorafenib against hepatocellular carcinoma. (30th September 2022) - Zhu, Xiao‐Feng; Sun, Zhong‐Lin; Ma, Jing; Hu, Bo; Yu, Min‐Cheng; Liu, Xiu‐Jie; Yang, Ping; Xu, Yang; Ju, Dianwen; Mu, Qing
Abstract: Sorafenib (SF), a multi‐kinase inhibitor, is the first FDA‐approved systemic chemotherapy drug for advanced hepatocellular carcinoma (HCC). However, its clinical application is limited by severe toxicity and side effects associated with high applied doses. Sophora alopecuroides L. is traditionally used as Chinese herbal medicine for treating gastrointestinal diseases, bacillary dysentery, viral hepatitis, and other diseases, and exerts an important role in anti‐tumor. Hence, we investigated the synergistic actions of seventeen flavonoids from this herb combined with SF against HCC cell lines and their primary mechanism. In the experiment, most compounds were found to prominently enhance the inhibitory effects of SF on HCC cells than their alone treatment. Among them, three compounds leachianone A (1 ), sophoraflavanone G (3 ), and trifolirhizin (17 ) exhibited significantly synergistic anticancer activities against MHCC97H cells at low concentration with IC50 of SF reduced by 5.8‐fold, 3.6‐fold, and 3.5‐fold corresponding their CI values of 0.49, 0.66, and 0.46 respectively. Importantly, compounds 3 or 17 combined with SF could synergistically induce MHCC97H cells apoptosis via the endogenously mitochondrial‐mediated apoptotic pathway, involving higher Bax/Bcl‐2 expressions with the activation of caspase‐9 and ‐3, and arrest the cell cycle in G1 phases. Strikingly, this synergistic effect was also closely related to the co‐suppression of ERK and AKT signaling pathways. Furthermore, compound 3 significantly enhanced the suppression of SF on tumor growth in the HepG2 xenograft model, with a 79.3% inhibition ratio at high concentration, without systemic toxicity, compared to either agent alone. These results demonstrate that the combination treatment of flavonoid 3 and SF at low doses exert synergistic anticancer effects on HCC cells in vitro and in vivo.